Social Responses to Mexico’s Economic Crisis of the 1980s - Hodara, Joseph (Frontera Norte, 2017)
San Diego, Center for US-Mexican Studies-University of California, 1991 (US-Mexico Contemporary Perspective Series, I), 244 págs. Mercedes González de la Rocha y Agustín Escobar Latapí(eds.),